Incidence of various medication errors in pediatrics in a tertiary care hospital - Dr. Chandra Deve Varma BSK; Dr. Balaji Bhusan Patnaik; Dr. Ratakonda Sruthi; Dr. Gangavaramsravankumar Reddy; Dr. V. Venkatesh; Dr. Jogi satyasree (Pediatric Review: International Journal of Pediatric Research, 2018)
Background: Medication errors in pediatrics are an important cause of iatrogenic disease in hospital patients[1]. Despite this, studies regarding the medication errors in India are very few.Aims: To determine the incidence and type of errors in a tertiary care hospital over a period of 4 months.Material and methods: It is a prospective observational study. Medication errors were documented instandard reporting forms from April 2018 to July 2018. Main outcome measures were incidence and types of medication errors in pediatrics.Results:The medication error was 1 per 9.5 patients i.e, 10.5%.The dispensing errors and clerical errors constituted 66.04% of all errors. Maximum medication error was found under the age of 2 years (49.07%). Incorrect IV infusion rate was 24.90% followed by prescribing incorrect dose 21.97%. Most common drugs implicated in medication errors were IV fluids followed by IV antibiotics.Conclusion: Adequate number of staff and electronic mode of prescription and compulsory documentation of errors will reduce iatrogenic errors significantly.